2020
DOI: 10.1108/ijaim-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing in India: evidence from accounting students and professionals

Abstract: Purpose The purpose of this paper is to examine whistleblowing behavior in the accounting community (students and professionals) in an emerging economy – India. Design/methodology/approach Using a case-based approach, data were collected from 263 accounting students and 268 accounting professionals in India. Findings Using multivariate and univariate analyses of variance and logistic regressions, the authors provided evidence on how accounting students and professionals behave in a whistleblowing environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
5
0
3
Order By: Relevance
“…Their superior moral reasoning is possibly the result of age, experience, increased proximity of consequences, maturation and/or education. Our results confirm earlier work on the primacy of business practitioners over students (Brody et al, 2020; Curtis et al, 2017; Ford & Richardson, 1994; Kraft & Singhapakdi, 1991; O'Fallon & Butterfield, 2005; Wood et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Their superior moral reasoning is possibly the result of age, experience, increased proximity of consequences, maturation and/or education. Our results confirm earlier work on the primacy of business practitioners over students (Brody et al, 2020; Curtis et al, 2017; Ford & Richardson, 1994; Kraft & Singhapakdi, 1991; O'Fallon & Butterfield, 2005; Wood et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…That is, Italian culture is posited as impacting the finding that there was a difference in evaluating layoffs but no difference in evaluating bank loans (Curtis et al, 2017). Continuing, while professionals and students tended to agree on issues surrounding whistleblowing, professionals in India were more concerned with fixing problems arising from whistleblowing than their student counterpart (Brody et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kaplan et al (2009) agreed with this result but he suggested that this result is true only when an anonymous reporting arrangement was available. Many scholars found that age is the important factor in business ethics maturity (Brody et al, 2020; Carrol and Cannon (1997); Ermasova et al, 2017, 2018; Loe et al, 2000; Nguyen et al, 2019). According to Loe et al (2000), the review of empirical articles found that nearly 50% of relevant studies found significant positive relationships between age and ethical judgments.…”
Section: Knowledge-stock Analysis: Major Trends and Topicsmentioning
confidence: 99%
“…It is worth noting that organisational retaliation targeting whistleblowers are always very evident and almost immediate in public administration in developing countries, where administrators are more socially embedded in one another, and whose interests or loyalty lie either in political or social groups than with the organisational or 'public interest' (e.g. Jamil 2002;De Maria 2005;Brody et al 2020). Uys and Senekal (2008) refers to this as morality of loyalty which they contrast with morality of principle, underpinned in the legal-rational principles of whistleblowing in public bureaucracies.…”
Section: Introductionmentioning
confidence: 99%